Silica-scaled chrysophytes of Lake Baikal - Bessudova, A. Yu.; Domysheva, V. M.; Firsova, A. D.; Likhoshway, Y. V. (Acta Biologica Sibirica, 2017)
The list of silica-scaled chrysophytes of Lake Baikal has been enlarged using electron microscopy. It has been supplemented with 12 species and 2 forms. Spiniferomonas takahashii has been observed for the first time in the water bodies of Russia. According to our data, the list of silica-scaled chrysophytes of Lake Baikal includes 25 species and intra-species taxa: Chrysosphaerella – 3, Paraphysomonas – 2, Clathromonas – 1, Spiniferomonas – 7, Mallomonas – 8 and Synura – 4. We have also analyzed their seasonal dynamics and observed algal species that are dominant in spring, summer and autumn.